Nest reuse by Pale-breasted Thrushes reduces the chance of cowbird parasitism and allows earlier initiation of breeding - Batisteli, Augusto Florisvaldo; Sarmento, Hugo; Aurelio Pizo, Marco [UNESP] (Wiley-Blackwell, 2021)
Selection of safe nest sites is a first step toward improving the chances of breeding successfully. Reusing old nests can save time and energy for breeding birds, but nest reuse is rare among open-cup nesting songbirds and the factors contributing to this behavior and its consequences for reproductive output remain little known. We studied an urban population of Pale-breasted Thrushes (Turdus leucomelas) in southeastern Brazil to determine whether nest reuse (1) was more likely after a successful nesting attempt both within and between breeding seasons, (2) affected the number of fledglings in the next nesting attempt, (3) reduced the chances of nest parasitism by Shiny Cowbirds (Molothrus bonariensis), and (4) was associated with earlier initiation of nests at the beginning of breeding seasons and shorter re-nesting intervals within breeding seasons. We monitored 266 nests from 2010 to 2019 and obtained data on 130 re-nesting events by individually marked birds. Nest reuse was more frequent after successful nesting attempts within breeding seasons. New nests were more likely to be parasitized by cowbirds, which had a negative effect on the number of fledglings per clutch. Reusing nests allowed earlier initiation of breeding at the start of breeding seasons, but did not shorten re-nesting intervals within seasons. Nest reuse by Pale-breasted Thrushes followed the win-stay lose-switch strategy and corroborated the time-saving hypothesis. Our results suggest that nest reuse may increase the fitness of Pale-breasted Thrushes by reducing the likelihood of cowbird parasitism.
Keywords: cowbird parasitism; breeding behavior; nest site selection; Turdus; win‐ stay lose‐ switch